Ecofeminist Theologies in the Age of Climate Crisis - Eaton, Heather (Feminist theology, 2021)
A few decades ago, ecofeminist historical efforts provided decisive revelations and analyses of the historical entanglements and parallel oppressions of women and nature: a women/nature nexus. Ecofeminism(s) are experiencing a resurgence, with fresh voices in new contexts, and addressing a wide range of concerns. It is encouraging that the relevance of the intersections of gender/nature and feminism and ecology is being reconsidered in new ways. This chapter addresses the topics of ecofeminism, climate change and related theological considerations. After an introduction to ecofeminisms and their debates, the discussion moves to ecofeminism and climate justice, ecological rights, planetary frameworks and the need for inspiring visions, especially in a (post)-COVID era.